Heavy vehicle path stability control for collision avoidance applications - Nozad, Arman (My University, 2011)
The current state of the art for Advanced Driver Assistant System (ADAS) in heavy trucks is based on pure braking interventions for rear-end collisions on highways and rural roads. In order to expand the scope to more general target scenarios, it is necessary to integrate braking and steering for more advanced interventions. The investigated target scenarios, which will cover not only rear-end collision, but also lateral conflicts and head-on collisions, are developed and prioritized based on accident statistics. For advanced interventions not only the speed of the truck but also the path should be under control. In fact the appropriate path controller should be applicable to various target scenarios and robust to variations in loading conditions. The overall goal of this work is to develop a path controller for a heavy vehicle based on integrated braking and steering, for collision avoidance application in the prioritized target scenarios. To determine the potential of various actuator configurations to avoid the collision, an optimal control problem is formulated and solved for each scenario. The solution provides the requirements for the actuators and a bench mark for the developed optimal path controller. For vehicle implementation a robust controller which is capable of dealing with disturbances and uncertainties is needed. The performance of the path controller in each target scenario and the sensitivity to key parameters is studied by performing the simulation on a detailed vehicle model. The target scenarios will be further prioritized based on the performance and robustness of the integrated braking and steering path controller. As a result of this work, a path stability controller which is capable of integrating the steering and braking actuators during the manoeuvre will be provided. Therefore a robust path controller for Advanced Driver Assistant System can be provided which can handle not only rear end collision scenarios but also head-on and lateral conflicts for heavy trucks. This work can be a new constructive step in Heavy truck active safety and autonomous collision avoidance manoeuvre that extends the area in which active safety system participate to reduce the amount of accidents as much as possible.
Keywords: Energi; Innovation och entreprenörskap (nyttiggörande); Transport; Teknisk mekanik; Övrig teknisk mekanik; Energy; Innovation & Entrepreneurship; Transport; Applied Mechanics; Other engineering mechanics